Helmet wearing and traumatic brain injuries among motorcyclists in Cotonou - TIDJANI, FIACRE; CHIGBLO, SEGLA PASCAL ERIC; HOUANNOU, VALENTIN; ALIHONOU, THIERRY; LAWSON, ERIC; AGBELELE, PENANCE; MADOUGOU, SOUMAILA; HANS MOEVI, ARISTOTE (My University, 2018)
Helmet wearing and traumatic brain injuries among motorcyclists in Cotonou
Keywords: Helmet wearing; traumatic brain injuries; motorcyclists; Cotonou